Ancient Greek medicine in questions and answers (Leiden ; Boston)
xi, 242 sayfa
Keywords: “This volume provides a set of in-depth case studies about the role of questions and answers (Q&A) in ancient Greek medical writing from its Hippocratic beginnings up to, and including, Late Antiquity. The use of Q&A formulas is widely attested in ancient Greek medical texts, casting an intriguing light on its relevance for the medical art at large, and for ancient medical practice, education, and research in specific (diagnostics, didactics, dialectics). The book aims to break new grounds by exploring, for the first time, the wide complexity of this phenomenon while introducing a coherent approach. In so doing, it not only covers highly specialized medical treatises but also non-canonical authors and texts, including anonymous papyrus fragments and collections of problems.“ --